DNA-based authentication in meat products: Quantitative detection of species adulteration and compliance issues - Styliani Minoudi; Konstantinos Gkagkavouzis; Nikoleta Karaiskou; Thomai Lazou; Alexandros Triantafyllidis (Applied Food Research)
Authenticity issues in meat products are recorded worldwide despite well-established food labeling regulations. Insufficient cleaning and sanitation in the food industry could justify the detection of undeclared species, but even trace amounts of swine and bovine meat may raise social, religious, and health concerns. This study aims to validate quantitative species-specific molecular methods using real-time PCR for animal species identification (bovine, chicken, horse, and swine) by assessing their sensitivity, specificity, and efficiency. These methods were subsequently applied to a total of 100 meat-related products from the Greek retail market to investigate possible mislabeling cases. The results showed that completely accurate labeling was observed only in 10% of samples. In contrast, considering EU Regulation about food fraud, the deliberate adulteration rate was estimated at 16%, with chicken being the most frequently undeclared species. For the first time in Greece, meat composition on food labels was quantitatively assessed. Notably, the declared pork percentage matched the quantitative results in only 10% of labeled samples. Specific commercial brands demonstrated better compliance compared to others. Despite inherent challenges in quantification, the results reveal significant authenticity issues supporting the need for continuous and well-documented monitoring of meat origin in the Greek and European food supply chain.